Fund-raising fundamentals : a guide to annual giving for professionals and volunteers - Greenfield, James M., 1936- (Nonprofit law, finance, and management series., 1994)
Every nonprofit organization relies on annual giving as the chief means of raising funds for its yearly operations as well as for maintaining the quality of its programs and expanding the services it provides for the public benefit. A step-by-step, hands-on guide to the basic techniques of annual giving campaigns, this book covers direct mail solicitation (including when to mail, to whom, and how often); membership drives; gift renewals; groups, guilds, and support organizations; benefits, activities, and special events; volunteer fund-raising (including how to recruit and train volunteer solicitors); premiums, advertising, and coupons; cause-related marketing and affinity cards; gambling and games of chance; door-to-door and on-street solicitation; multimedia options and telemarketing; television and telethon solicitation.